Polyunsaturated fatty acid profiles of whole body phospholipids and triacylglycerols in anadromous and landlocked Atlantic salmon (Salmo salar L.) fry. - Peng, Jinglan; Larondelle, Yvan; Pham, Diep; Ackman, Robert G; Rollin, Xavier (Elsevier Inc., 2003)
We compared the fatty acid compositions and gains of whole body triacylglycerols (TAG) and phospholipids (PL) in anadromous and landlocked Atlantic salmon (Salmo salar) fry, of the same age, fed the same commercial marine oil-rich diet over a 42-day feeding trial. The landlocked strain exhibited significantly (P<0.05) higher growth rate and feed efficiency, due principally to a higher fat retention, particularly of monounsaturated and saturated fatty acids (SFA). n-3 and n-6 long-chain polyunsaturated fatty acid (PUFA) gains and retentions were significantly higher (P<0.05) in the landlocked fry. Great similarities were found in the fatty acid profiles of whole body TAG of both strains. However, marked genotypic differences were observed in the PUFA profiles of whole body PL fractions. The total PUFA, n-3 PUFA and docosahexaenoic acid (DHA) level in PL was significantly higher (P<0.05) while the SFA level, and the PUFA C18/C20 and eicosapentaenoic acid/arachidonic acid ratios were significantly lower (P<0.05) in the anadromous fry than in landlocked fry. Our results indicate that the level of DHA in salmon PL is under strong genetic control and that the capacity for incorporation, and possibly for the conversion of dietary n-3 and n-6 PUFA, is higher in the landlocked strain.